Potential challenges and future implications for trauma-informed approaches in schools - Phung, Binh (Frontiers in Education, 2022)
Adverse childhood experiences (ACEs) refer to a collection of traumatic life events that can derail future development, impact physical/mental health, and affect learning/behavior into adulthood. In the United States, it is estimated that two-thirds of children and teens will experience traumatic ACEs by the age of 16. Schools can represent one domain in a child’s life where trauma-informed approaches (TIAs) could be helpful to curtail effects of ACEs. This systematic review aimed to identify some positive commonalities/facilitators (e.g., drivers of change) among existing TIAs implemented in U.S. schools. The secondary objectives aimed to evaluate the confidence of qualitative data using GRADE-CERQual and to highlight potential challenges/barriers associated with the implementation process of TIAs in schools. This manuscript presents a thorough overview of the current state of trauma-informed practices in U.S. schools and concludes with a forward-thinking discussion on key implications for enhancing the field of education.